Controlled Growth of Large-Area Aligned Single-Crystalline Organic Nanoribbon Arrays for Transistors and Light-Emitting Diodes Driving - Wang, Wei; Wang, Liang; Dai, Gaole; Deng, Wei; Zhang, Xiujuan; Jie, Jiansheng; Zhang, Xiaohong (Nano-Micro Letters, 2017)
Organic field-effect transistors (OFETs) based on organic micro-/nanocrystals have been widely reported with charge carrier mobility exceeding 1.0 cm2 V−1 s−1, demonstrating great potential for high-performance, low-cost organic electronic applications. However, fabrication of large-area organic micro-/nanocrystal arrays with consistent crystal growth direction has posed a significant technical challenge. Here, we describe a solution-processed dip-coating technique to grow large-area, aligned 9,10-bis(phenylethynyl) anthracene (BPEA) and 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS-PEN) single-crystalline nanoribbon arrays. The method is scalable to a 5 × 10 cm2 wafer substrate, with around 60% of the wafer surface covered by aligned crystals. The quality of crystals can be easily controlled by tuning the dip-coating speed. Furthermore, OFETs based on well-aligned BPEA and TIPS-PEN single-crystalline nanoribbons were constructed. By optimizing channel lengths and using appropriate metallic electrodes, the BPEA and TIPS-PEN-based OFETs showed hole mobility exceeding 2.0 cm2 V−1 s−1 (average mobility 1.2 cm2 V−1 s−1) and 3.0 cm2 V−1 s−1 (average mobility 2.0 cm2 V−1 s−1), respectively. They both have a high on/off ratio (I on/I off) > 109. The performance can well satisfy the requirements for light-emitting diodes driving. Highlights: 1 A simple solution-processed dip-coating method achieves large-area single-crystalline nanoribbon arrays (5 × 10 cm2). High-performance organic field-effect transistors (OFETs) can be obtained through this method. 2 Organic nanoribbon array-based OFETs exhibit long-time cycle stability, enabling the control of light emission of different pixel patterns of LEDs.